Unconventional Monetary Policy, Fiscal Side Effects and Euro Area (Im)balances - Michael Hachula; Michele Piffer; Malte Rieth (Journal of the European Economic Association, 2020)
We study the macroeconomic effects of unconventional monetary policy in the euro area using structural vector autoregressions, identified with external instruments. The instruments are based on the common unexpected variation in euro area sovereign yields for different maturities on policy announcement days. We first show that expansionary monetary surprises are effective at lowering public and private interest rates and increasing economic activity, consumer prices, and inflation expectations. We then document that the shocks lead to a rise in primary public expenditures and a widening of internal trade balances.
Keywords: 330